The impact of participation in global value chains of services on per capita GDP: Standard study for a group of developing countries in the period: 2000-2017 - Bouchoul, Said; Djermoun, Souad (Dirassat Journal Economic Issue, 2020)
The study aimed to measure the impact of participation in global value chains of services on per capita GDP in 15 developing countries for the period 2000-2017, by estimating a standard model using Eviews10 and Stata14. And the results of estimating the model using the combined PMG method indicated that the per capita GDP is related to a direct relationship with the variables of the value-added share of domestic and foreign services from the total exports (FVASH, DVASH), the competitive variable of industrial performance CIP and MD money supply, Final consumer spending, as the industrial performance competitiveness index is the most influential per capita gross domestic product.